2013
DOI: 10.1371/journal.pone.0058416
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Variation in a Dominant Tree Species: Population Divergence, Selection and Genetic Stability across Environments

Abstract: Understanding among and within population genetic variation of ecologically important plant traits provides insight into the potential evolutionary processes affecting those traits. The strength and consistency of selection driving variability in traits would be affected by plasticity in differences among genotypes across environments (G×E). We investigated population divergence, selection and environmental plasticity of foliar plant secondary metabolites (PSMs) in a dominant tree species, Eucalyptus globulus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 66 publications
0
15
1
Order By: Relevance
“…Common-environment field trials based on OP progenies collected from native populations indicated that there is marked quantitative genetic differentiation between northern and southern races, with northern populations having greater bark thickness [27]; wood with more extractives and lignin content, and a higher syringyl/guaiacyl ratio [70]; later transition to adult foliage [71]; more resistance to leaf disease [72] and drought [28]; and tending to be generally slower growing than southern races [73], [74]. There are also differences in foliar chemistry [42], [75], [76] and marsupial herbivory [77] that could partly explain the fitness differences we have observed. A specific study undertaken on the Geeveston trial at age 3 years showed that the northern trees (♀ N ♂ N ) were more susceptible to marsupial herbivory than southern trees (♀ S ♂ S ) in the field and in artificial feeding trials, most likely due to their foliage containing more tannins and essential oils [78].…”
Section: Discussionmentioning
confidence: 99%
“…Common-environment field trials based on OP progenies collected from native populations indicated that there is marked quantitative genetic differentiation between northern and southern races, with northern populations having greater bark thickness [27]; wood with more extractives and lignin content, and a higher syringyl/guaiacyl ratio [70]; later transition to adult foliage [71]; more resistance to leaf disease [72] and drought [28]; and tending to be generally slower growing than southern races [73], [74]. There are also differences in foliar chemistry [42], [75], [76] and marsupial herbivory [77] that could partly explain the fitness differences we have observed. A specific study undertaken on the Geeveston trial at age 3 years showed that the northern trees (♀ N ♂ N ) were more susceptible to marsupial herbivory than southern trees (♀ S ♂ S ) in the field and in artificial feeding trials, most likely due to their foliage containing more tannins and essential oils [78].…”
Section: Discussionmentioning
confidence: 99%
“…Asterisks indicate significance ( P < 0.05), with boldface indicating significance after a Bonferroni adjustment to P = 0.0035. Q st values significantly different from the reported average F st (0.09) between sub‐races for microsatellite markers are shown in boldface, with asterisks indicating Q st values significantly different from the recorded maximum F st (0.201) (see O'Reilly‐Wapstra et al ., ). Statistical significance was tested using a Wald F ‐test for the fixed sub‐race effect.…”
Section: Methodsmentioning
confidence: 97%
“…Genetic‐based variation in wax chemistry at the sub‐race and family within sub‐race levels was studied by growing families with known female pedigrees in a replicated common environment field trial (Hamilton et al ., ; O'Reilly‐Wapstra et al ., ); located at Salmon River (41°01′S, 144°52′E) in northwest Tasmania, Australia. The trial was established in 2006 using progeny derived from open‐pollinated seed (families) from 140 trees sampled across the natural range of E. globulus .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the rationale is that variance in such traits may indicate different coexisting optima-a sign of spatially or temporally variable selection and adaptation. Some pioneering studies have shown that natural forest populations studied in situ display heritability for fitnessrelated traits, such as chemical traits associated to herbivore resistance in eucalypts (O'Reilly-Wapstra et al 2013) and white spruce (Mageroy et al 2014), serotiny and growth traits in Mediterranean pines (Budde et al 2014;Alía et al 2014) and leaf functional traits in cork oak (Ramírez-Valiente et al 2014). More results of the same kind are available in beech (Bontemps et al, in preparation).…”
Section: Microgeographic Variation In Forest Trees: State Of the Artmentioning
confidence: 99%